Approaches for integrating information from radiation biology and epidemiology to enhance low-dose health risk assessment : recommendations of the National Council on Radiation Protection and Measurements. (National Council on Radiation Protection and Measurements, 2020)
"This Report extends the concepts and approaches discussed in NCRP Report No. 171 and Commentary No. 24 to further reduce uncertainty in radiation risk assessments at low doses and low dose rates, thereby enhancing the bases for radiation protection guidance"-- Provided by publisher.
This Report addresses the conclusions and recommendations from three previous NCRP Reports and Commentaries on the topic of the risks of adverse health outcomes at low doses and low dose rates of ionizing radiation (NCRP, 2012; 2015; 2018a).
Keywords: Ionizing radiation.; Radiation -- Dosage.; Low-level radiation -- Dose-response relationship.; Radiation -- Health aspects.; Health risk assessment.; Risk assessment.; elektronické knihy; electronic books